Evaluation of a Software Architecture Supporting Android Applications for Users with Motor Disabilities - Machado-Neto, Olibário José; Pimentel, Maria da Graça Campos (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2017)
A software architecture is an organization that contains the structure of a software and the relationship of its components. As a result, software architectures dictate the way software is created and updated. We propose a software architecture to help developers to create Android-based applications for users with motor disabilities – specifically. The architecture supports using one or more hardware components of mobile devices including built-in sensors, camera and microphone. Also, it encompasses a straightforward way of using and integrating such resources, which may lead to applications that provide alternative ways for accessing and managing data by users with disabilities. The solution also provides functionalities to work with raw sensor data, and offers a model for storing medical information of users. An evaluation with 19 software developers indicate that the architecture can be useful for creating not only solutions for people with motor disabilities, but diverse applications